Effect of visco‐elastic silk–chitosan microcomposite scaffolds on matrix deposition and biomechanical functionality for cartilage tissue engineering. (7th April 2015) - Chameettachal, Shibu; Murab, Sumit; Vaid, Radhika; Midha, Swati; Ghosh, Sourabh
Abstract: Commonly used polymer‐based scaffolds often lack visco‐elastic properties to serve as a replacement for cartilage tissue. This study explores the effect of reinforcement of silk matrix with chitosan microparticles to create a visco‐elastic matrix that could support the redifferentiation of expanded chondrocytes. Goat chondrocytes produced collagen type II and glycosaminoglycan (GAG)‐enriched matrix on all the scaffolds (silk:chitosan 1:1, 1:2 and 2:1). The control group of silk‐only constructs suffered from leaching out of GAG molecules into the medium. Chitosan‐reinforced scaffolds retained a statistically significant ( p  < 0.02) higher amount of GAG, which in turn significantly increased ( p  < 0.005) the aggregate modulus (as compared to silk‐only controls) of the construct akin to that of native tissue. Furthermore, the microcomposite constructs demonstrated highly pronounced hysteresis at 4% strain up to 400 cycles, mimicking the visco‐elastic properties of native cartilage tissue. These results demonstrated a step towards optimizing the design of biomaterial scaffolds used for cartilage tissue engineering. Copyright © 2015 John Wiley & Sons, Ltd.